2018
DOI: 10.1038/s41598-018-27678-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal role of the inferolateral prefrontal cortex in balancing goal-directed and habitual control of behavior

Abstract: Successful adaptation to complex environments depends on the balance of at least two systems: a flexible but slow goal-directed system encoding action-outcome associations and an efficient but rigid habitual system linking responses to preceding stimuli. Recent evidence suggests that the inferolateral prefrontal cortex (ilPFC), a region well known to contribute to cognitive control processes, may play a crucial role in the balance of goal-directed and habitual responding. This evidence, however, comes mainly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…We also successfully replicated previous findings supporting the neural hypothesis of arbitration control. We found the max reliability signal, the key signal used to mediate arbitration between model-based and model-free RL, in the bilateral inferior lateral PFC (ilPFC, left: p<0.05 in cluster-level corrected; right: p<0.05 in small-volume corrected [SVC] at [8,6,-2]) and the frontopolar cortex (FPC, p<0.05 in cluster-level corrected), fully consistent with previous results 25,29 (Figure 4, Supplementary Table S3).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We also successfully replicated previous findings supporting the neural hypothesis of arbitration control. We found the max reliability signal, the key signal used to mediate arbitration between model-based and model-free RL, in the bilateral inferior lateral PFC (ilPFC, left: p<0.05 in cluster-level corrected; right: p<0.05 in small-volume corrected [SVC] at [8,6,-2]) and the frontopolar cortex (FPC, p<0.05 in cluster-level corrected), fully consistent with previous results 25,29 (Figure 4, Supplementary Table S3).…”
Section: Resultssupporting
confidence: 89%
“…We found that the effect size (parameter estimates from the GLM analysis) of the max reliability signal for FPC ([8,44,40], z=3.83) was negatively correlated with the depression score (estimated correlation coefficient=-0.441, p =0.019; Figure 6b). Moreover, the effect sizes of the max reliability signal for the bilateral ilPFC ([-52,26,16], z-score=4.48; [42,20,-8], z-score=3.61) and FPC ([8,44,40], z-score=3.83), the brain areas previously implicated in arbitration control 25,29,41 , tended to be lower in the depressive group (CES-D score≤16) than in the control group (CES-D score<16) (Figure 6c, left; one-way ANOVA; F 1,26 =2.76 [ p =0.108], F 1,26 =2.93 [ p =0.099], F 1,26 =5.18 [ p =0.031] for the left and right ilPFC and FPC, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Resilience against the risk of developing addiction (either because drug use was not initiated despite increased genetic or social/environmental risk [unaffected siblings] or regular drug use had not transitioned into addiction [recreational stimulant users]) was associated with hyperconnectivity in two regulatory control networks: One network involved the right lateral prefrontal cortex (lPFC) (including the right IFG) and its connections to the vmCAU. This network is implicated in regulating selected actions ( 36 ) by down-regulating habitual control over behavior ( 37 ). The lPFC should be distinguished from the vmPFC, which is more associated with the representation of goals ( 28 ) and exhibits hypoconnectivity in participants with familial risk.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, the inhibition may not impact on the ability of those systems to make predictions in the first place, but only gate the extent to which that individual expert exerts influence on the output channel. A study by Bogdanov et al, (2018) also provided direct evidence that neuromodulation of vlPFC impacts the relative control of different expert systems. In that study, theta-burst TMS was used to inhibit activity in vlPFC while participants performed a slips-of-action task aimed at pitting goal-directed and habitual strategies.…”
Section: (2) Reliability Signals For Different Expertsmentioning
confidence: 97%